Gênese documental de álbuns fotográficos: um estudo de caso aplicado a uma indústria de grande porte - Pupim, Eliana Kátia [UNESP] (2010)
The following text presents informations about the need of a study in case of private file of a representative fotographic company of the social events business. There are three reazons for the choice of that company: 1) The opening of the company to academic reaserch interest; 2) the size of the file that nowadays keeps more than 100.000 documents/albums; 3) the fact that almost three years ago, the company adopted the digital system of images capture, and now its adapting its equipments, employees, photographers and the file to new technologies. The social study importance takes place through the proximity of a concrete tie between the professional and Information Science, with graduation in Marilia town and the photographic field in Tupã region, opening promising interchange channels in a not exploited area among companies and professionals. The scientific importance might be evaluated by means of knowledge construction that approaches Information Science and Archivology, encouraging the interdiciplinary discution about the photographic founds administration privates. The results of data collection were synthesized by a structural chart of the company's flow chart that describes the creation of the document containing all information relating to the final product of the company, as well as the construction of a functional organizational structure that allows us to understand the activities developed by sector Archive Albums